2019
DOI: 10.2147/ott.s219018
|View full text |Cite
|
Sign up to set email alerts
|

<p>miR-1271 inhibits growth, invasion and epithelial–mesenchymal transition by targeting ZEB1 in ovarian cancer cells</p>

Abstract: ObjectiveMicroRNA-1271 (miR-1271) has a role in suppressing cell growth, cell cycle and promoting cell apoptosis in many cancers. This research was to explore the great role of miR-1271 in ovarian cancer (OC).Patients and MethodsRT-qPCR was utilized to evaluate the mRNA levels of miR-1271 and its target gene. The proliferative and invasive abilities were measured using Cell Counting Kit-8 and transwell assays. The overall survival rate of OC patients was assessed by Kaplan–Meier method.ResultsmiR-1271 was down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In the case of osteosarcoma, it was demonstrated that miR-1271-5p inhibited cell proliferation and invasion by Wnt signaling [ 53 ]. A study in cell cultures reports inhibition of miR-1271-5p expression in ovarian cancer cells compared to normal [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of osteosarcoma, it was demonstrated that miR-1271-5p inhibited cell proliferation and invasion by Wnt signaling [ 53 ]. A study in cell cultures reports inhibition of miR-1271-5p expression in ovarian cancer cells compared to normal [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for EOC, our previous study uncovered that circ-ABCB10 expression is elevated in EOC cell lines compared with normal ovarian epithelial cells, and it increases cell proliferation, but decreases apoptosis and the expression of miR-1271, miR-1252 and miR-203 (9). miR-1271 serves as a tumor suppressive miRNA, which inhibits cell proliferation and invasion via modulating downstream target genes in various types of cancer (10,16,17). In EOC, miR-1271 inhibits cell viability, invasion and epithelial mesenchymal transition by directly binding to the 3'-untranslated region of zinc finger E-box binding homeobox 1 mRNA in EOC (17).…”
Section: Discussionmentioning
confidence: 99%
“…miR-1271 serves as a tumor suppressive miRNA, which inhibits cell proliferation and invasion via modulating downstream target genes in various types of cancer (10,16,17). In EOC, miR-1271 inhibits cell viability, invasion and epithelial mesenchymal transition by directly binding to the 3'-untranslated region of zinc finger E-box binding homeobox 1 mRNA in EOC (17). In colorectal cancer, miR-1271 promotes cell proliferation and invasion by suppressing Capn4 (10).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al indicated that miR-1271 blocks the development of papillary thyroid carcinoma via inhibiting IRS1 expression and inactivating the AKT signaling pathway [ 27 ]. Importantly, miR-1271 has been reported as a suppressive factor in OC cells, which suppresses growth and invasion through mediating epithelial-mesenchymal transition [ 28 ]. However, the specific molecular mechanism of miR-1271-5p in OC still needed to be detected.…”
Section: Discussionmentioning
confidence: 99%